A high-throughput platform for interpretation of metabolite profile data from pepper (Capsicum) fruits of 13 phenotypes associated with different fruit maturity states. (30th November 2020) - Kim, Tae Jin; Hyeon, Hyejin; Park, Nam Il; Yi, Tae Gyu; Lim, Sun-Hyung; Park, Soo-Yun; Ha, Sun-Hwa; Kim, Jae Kwang
Highlights: Metabolomics results of 131 metabolites were obtained from 26 pepper phenotypes. Carotenoids were correlated with the carotenoid-derived volatiles in pepper fruit. Our data reveal the accumulation of stress-related metabolites in mature pepper fruit. Abstract: Nowadays, novel tools have been developed for efficient analysis and visualization of large-scale metabolite profile data associated with metabolic pathways. A high-throughput platform using PathVisio 3 combined with multivariate analysis is proposed for the first time. Additionally, this is the first analysis of the relationships among terpenoids monoterpene, sesquiterpene, triterpene, and tetraterpene during pepper fruit ripening, and their changes. This platform was successfully applied to interpret large-scale data related to 131 metabolites from mature and immature fruits of 13 pepper phenotypes. The carotenoid-derived volatiles, such as dihydroactinidiolide and β-ionone were closely correlated with carotenoids, indicating that the synthesis and degradation of carotenoids occurred in pepper fruit mature stage. Using PathVisio 3, the metabolic changes in pathway could be presented quickly, revealing the accumulation of stress-related metabolites, such as proline, capsaicin, and phenylalanine, in the mature stage. This approach could provide useful information about comprehensive biochemical regulation of fruit ripening.